Experimentações em Rimbaud na "casa dos doidos" : pensando justiça espacial no estudo de caso de duas residências terapêuticas, em Cariacica-ES - Barbosa, Lohaine Jardim (2019)
This thesis seeks to exercise one dialogic relation with literature language of the Arthur Rimbaud and geography language while politic posture of the experimentation of one spatial in favor of advance in epistemological discussions, expensive to geography. This research begin from the poetic space of Arthur Rimbaud to discuss the coexistence and co-pertenciment concepts, propitiate a new perspectives and possibilities to spatial justice concept. The hypothesis to be verified, under this perspective, is that spatial justice, in social justice conditions, just occur in contexts of coexistence and co-pertenciment of peoples and spaces, and based in promotion and valorization of difference while positivity. In order to validate this hypothesis, was realize um field research in two TRs (Terapeutics Residences: houses used as habitations by ex-patients of psychiatric hospitals with aim of “social reintroduction”) located in Cariacica City, Espírito Santo State, and also carried out interviews with the neighborhood and the technicians of the state health service, responsible for attending to the residents. The field experience validates the importance of the concepts discussed to heal spatial and social injustices and the proposed humanistic and affective perspective can be of great value in overcoming the limitations of macrossocial approaches that reduce the concept of justice to its social component, expanding this debate and its importance in overcoming the injustices produced spatially in the globalized world.